Prevention and treatment of recurrent fractures after percutaneous vertebroplasty with denosumab in patients with osteoporotic vertebral compression fractures - Shouyu Xiang; Cheng Tang; Long Ling; Wei Liu; Bingwen Bai; Yanming Cao (Guoji laonian yixue zazhi)
[Objective] To investigate the preventive effect of denosumab on recurrent fractures after percutaneous vertebroplasty in patients with osteoporotic vertebral compression fractures. [Methods] A total of 72 patients diagnosed with osteoporotic vertebral compression fracture and treated by percutaneous vertebroplasty in the orthopedic department of the Second Affiliated Hospital of Guangzhou Medical University from January 2022 to December 2022 were selected as the study subjects.Patients were randomly divided into two groups, each had 36 cases.The control group received conventional anti-osteoporosis treatment, and the observation group added denosumab on the basis of control group treatment.Both groups were followed for 1 year, while the fracture rate and the levels of bone mineral density(BMD), visual analogue scale(VAS) score, oswestry disability index(ODI), beck value, sagittal cobb angle and procollagen type ⅠN-terminal propeptid(PINP) and β-carboxy-terminal cross-linked telopeptide of type Ⅰ collagen(β-CTX) were compared between the two groups. [Results] There was no significant preoperative on BMD, VAS score, ODI index,beck values, sagittal cobb angle, PINP and β-CTX levels between the two groups before the surgery(P>0.05); After postoperative follow-up of 6 months, BMD in the observation group was higher than that in the control group (P<0.05), while VAS score, ODI index, PINP and β-CTX levels were lower than those in the control group (P<0.05).At 1 year postoperative follow-up, BMD and beck values in the observation group were higher than those in the control group (P<0.05), while fracture rate, VAS score, ODI index, sagittal cobb angle and PINP and β-CTX levels were lower than those in the control group(P<0.05). [Conclusion] Denosumab treatment effectively relieves pain after percutaneous vertebroplasty in patients with osteoporotic vertebral compression fractures, promotes fracture healing, increases vertebral bone mineral density, and reduces the incidence of vertebral refractures.